2009
DOI: 10.1007/s11240-009-9560-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to in vitro shoot-tip necrosis and their physiological interactions

Abstract: Plant tissue culture plays an important role in the production and conservation of plant species. Its application, however, is hindered by some growth abnormalities such as shoot-tip necrosis (STN) caused by the culture conditions. This review article summarizes the literature published on the causes of in vitro STN in plants such as medium type, plant growth regulators, calcium, boron, medium additives, the culture environment, their interaction and physiological effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 67 publications
4
38
0
Order By: Relevance
“…-no significant differences; (-) -no regeneration or died during storage Several authors ascribed necrosis and browning during cold storage to the presence of light and found them to be less pronounced in darkness (Hausman et al 1994;Romano, Martins-Loução 1999) or when BAP was lacking in the storage medium (Orlikowska 1992). Furthermore, Bairu et al (2009) supposed that when plants are cultured in a cytokinin-free medium, cytokinins are depleted from the shoots; the absence of roots decreases the endogenous cytokinin level, stopping cell division and causing apical necrosis. However, this interpretation may not explain our cold chamber results.…”
Section: Resultsmentioning
confidence: 99%
“…-no significant differences; (-) -no regeneration or died during storage Several authors ascribed necrosis and browning during cold storage to the presence of light and found them to be less pronounced in darkness (Hausman et al 1994;Romano, Martins-Loução 1999) or when BAP was lacking in the storage medium (Orlikowska 1992). Furthermore, Bairu et al (2009) supposed that when plants are cultured in a cytokinin-free medium, cytokinins are depleted from the shoots; the absence of roots decreases the endogenous cytokinin level, stopping cell division and causing apical necrosis. However, this interpretation may not explain our cold chamber results.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of cytokinins is associated with the appearance of necrosis on explants during cold storage, but the lack of roots leads to a decrease in endogenous cytokinin biosynthesis and a consequent reduction in cell division (Bairu et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…After 2 weeks of culturing, necrotic apices were observed in shoots growing in semisolid medium provided with either diffused or forced ventilation. This physiological disorder is commonly seen in in vitro cultures affecting a wide range of herbaceous and woody plants (Bairu et al, 2009a) and it is caused by a complex set of factors including plant growth regulators (Bairu et al, 2009b), calcium and boron deficiency (Hepler, 2005;Martin et al, 2007), medium type and salt strength (Jain et al, 2009;Takura and Kanwara, 2011), gelling agent (Singha et al, 1990), aeration (Bairu et al, 2009a), and pH (Pasqua et al, 2002). Our results indicated that the use of liquid medium through a TI system could overcome the shoot tip necrosis of H. heptaphyllus and promote growth and rooting of shoots.…”
Section: Resultsmentioning
confidence: 99%